MANAGEMENT OF THE NATURAL RESOURCES OF THE MUNICIPALITY OF OCARA – CE: AN ANALYSIS ABOUT THE GREEN SEAL GRANT - de Araújo Maia, Magna Helena; da Silva, Natália Reis; Costa, Regilane Cunha; Lins, Gustavo Aveiro; de Almeida, Josimar Ribeiro (Revista Internacional de Ciências, 2012)
The current environmental of brazilian cities particulary the ones in the country side of the country's northeast make evident a scene of degradation due to the immense exploitation of natural resources what has been jeopardizing the productive potential of these resources, besides having influence on the low levels of quality of life of the population. Hence, some counties have been looking for solutions so their management processes may help in some way to minimize the harms caused by the exploitation of these resources. Inside this context is this county of Ocara which has been showing a very evident scene of degradation but it was awarded with the "selo verde" (green label) for its projects and environmental policies. This fact made necessary to analize why this county it was awarded with the green seal. To achieve this aim it was designed a project divided into 3 chapters: Chapter 01 – Concepts of management, public policies and environmental management and a presentation of the "selo verde"; Chapter 02 – Green seal concepts, historical data, methodology and requirements of evaluation and Chapter 03 – An case study is done in the county of Ocara.